Metode Sorogan Dalam Pembelajaran Membaca Al-Qur’an di Pondok Pesantren - Anwar, Chaerul (Al-Wasathiyah: Journal of Islamic Studies, 2022)
This study aims to reveal the effectiveness of reading the Qur'an using the sorogan method at the Al-Falah Lulut Islamic Boarding School and the factors that support and hinder the application of the method. With this research, it is hoped that it can provide new input to all parties involved in the art of reading the Qur'an in general and in particular the Al-Falah Lulut Islamic Boarding School as the place of this research. This research is a qualitative research, taking the background of Al-Falah Lulut Islamic Boarding School. Data collection is done by conducting interviews, observations, documentation, and literature review. The data analysis used is qualitative analysis. Qualitative analysis is used to analyze data that is not in the form of numbers, namely the deductive method. The results showed: The results of learning to read the Qur'an using the sorogan method for categories level one, two, and three are quite effective, in the learning process the children are very happy, but in the application of the sorogan method, it is largely determined by the abilities and skills of the tutor ustadz , because the sorogan system in teaching is the most difficult system of the entire Islamic education system.